MARKETING TRAINING FOR ALFALAND GROUP EMPLOYEES: USING TIKTOK AS A MARKETING TOOL - Fahrul Riza; Lanang Diayudha; Ongky Alex Sander; Oktafalia Marisa Muzammil; Tannia; Andreas Wijaya; Danny Santoso (Rural Development For Economic Resilience (RUDENCE), 2022)
Companies are increasingly turning to social media as a tool to support their commercial activities. According to AppAnnie's poll, TikTok has surpassed Instagram as the most downloaded social media app since 2018. TikTok appeals to people of all ages because of its algorithmic capacity to detect user preferences and short content duration. The Bunda Mulia University Management Study Program and Alfaland Group, a company that specialises in property management, collaborated on this community service activity titled "Marketing 101: TikTok Marketing for Business." The service firm faces a major revenue difficulty as a result of the adoption of Community Activity Restrictions (PPKM). The goal of this activity is to encourage employees from PT Alfaland's operational and marketing divisions how to use TikTok as a marketing tool. Employees from branches around Indonesia took part in the training, which was delivered entirely online. The training materials included an introduction to the TikTok application as well as measurement tools for tracking marketing effectiveness. This service resulted in the creation of creative content by participants to promote Alfa-land products and services, as well as an increase in staff creativity, particularly in the operational and marketing divisions, in marketing services from AlfaLand. Employee input on using the TikTok application for marketing included flexible cost control, the ability to watch the viewer in real time, audience targeting, and tracking customer feedback.